Japan 2026 - Hoy, Selena Takigawa; Bartlett, Ray; Goss, Rob; Hughes, Felicity (Travel journalist); Korteman, Jessica; McLachlan, Craig, 1962-; Milner, Rebecca; Tan, Winnie (Travel writer); Tang, Phillip; Yanagihara, Wendy (Lonely Planet guidebooks., 2026)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime in this latest edition of our guide to Japan. Discover Japan's most popular experiences and best kept secrets from hitting the slopes of Niseko, Asia's top ski and snowboarding destination; to taking in Kyoto's Gion district while looking out for geisha shuffling the lantern-lit streets; and travelling the long and winding road to Nyuto Onsen, one of Japan's most rustic hot-spring experiences.